Dysfunction of basal ganglia functional connectivity associated with subjective and cognitive fatigue in multiple sclerosis - Langley, Christelle; Masuda, Naoki; Godwin, Simon; De Marco, Giovanni; Smith, Angela Davies; Jones, Rosemary; Bruce, Jared; Thai, Ngoc Jade (Frontiers in Neuroscience, 2023)
Objectives Central fatigue is one of the most common symptoms in multiple sclerosis (MS). It has a profound impact on quality of life and a negative effect on cognition. Despite its widespread impact, fatigue is poorly understood and very difficult to measure. Whilst the basal ganglia has been implicated in fatigue the nature of its role and involvement with fatigue is still unclear. The aim of the present study was to establish the role of the basal ganglia in MS fatigue using functional connectivity measures. Methods The present study examined the functional connectivity (FC) of the basal ganglia in a functional MRI study with 40 female participants with MS (mean age = 49.98 (SD = 9.65) years) and 40 female age-matched (mean age = 49.95 (SD = 9.59) years) healthy controls (HC). To measure fatigue the study employed the subjective self-report Fatigue Severity Scale and a performance measure of cognitive fatigue using an alertness-motor paradigm. To distinguish physical and central fatigue force measurements were also recorded. Results The results suggest that decreased local FC within the basal ganglia plays a key role in cognitive fatigue in MS. Increased global FC between the basal ganglia and the cortex may sub serve a compensatory mechanism to reduce the impact of fatigue in MS. Conclusion The current study is the first to show that basal ganglia functional connectivity is associated with both subjective and objective fatigue in MS. In addition, the local FC of the basal ganglia during fatigue inducing tasks could provide a neurophysiological biomarker of fatigue.